Improving outcomes from high-risk surgery: a multimethod evaluation of a patient-centred advanced care planning intervention. Issue 2 (27th February 2017) - Selwood, Amanda; Senthuran, Siva; Blakely, Brette; Lane, Paul; North, John; Clay-Williams, Robyn
Abstract : Introduction: Patients who are frail, have multiple comorbidities or have a terminal illness often have poor outcomes from surgery. However, sole specialists may recommend surgery in these patients without consultation with other treating clinicians or allowing for patient goals. The Patient-Centred Advanced Care Planning (PC-ACP) model of care provides a framework in which a multidisciplinary advanced care plan is devised to incorporate high-risk patients' values and goals. Decision-making is performed collaboratively by patients, their family, surgeons, anaesthetists, intensivists and surgical case managers. This study aims to evaluate the feasibility of this new model of care, and to determine potential benefits to patients and clinicians. Methods and analysis: After being assessed for frailty, patients will complete a patient–clinician information engagement survey pretreatment and at 6 months follow-up. Patients (and/or family members) will be interviewed about their experience of care pretreatment and at 3 and 6 months follow-ups. Clinicians will complete a survey on workplace attitudes and engagement both preimplementation and postimplementation of PC-ACP and be interviewed, following each survey, on the implementation of PC-ACP. We will use process mapping to map the patient journey through the surgical care pathway to determine areas of improvement and to identify variations in patient experience. Ethics and dissemination: This study has received ethical approval from Townsville Hospital and Health Service HREC (HREC/16/QTHS/100). Results will be communicated to the participating hospital, presented at conferences and submitted for publication in a peer-reviewed MEDLINE-indexed journal.